Evaluasi Strategi Guru PAI dalam Meningkatkan Kedisiplinan Siswa - Sintasari, Beny; Lailiyah, Nurul; Rozaq, Abd (Ngaos: Jurnal Pendidikan dan Pembelajaran, 2024)
This research aims to describe the efforts of Islamic Religious Education teachers in improving student discipline at SMP Plus Al Hidayah Sugihwaras Parengan Tuban, as well as identifying supporting and inhibiting factors. The research method used was descriptive qualitative with research subjects including school principals, PAI teachers, and class VII students. Data collection techniques are carried out through observation, interviews, and documentation. The research results show that the efforts made by PAI teachers are quite diverse, such as example, habituation, supervision, giving advice, motivation, and punishment. However, some students still lack discipline, especially when attending Dhuha prayers in the congregation. Factors that influence student discipline are divided into internal factors, such as difficulty getting up in the morning and managing time, and external factors, such as lack of parental attention. Even though the efforts are based on the concept of character education, continuous evaluation, and improvement are still needed by involving all related parties to be more effective in forming students' disciplined characters. Efforts to improve discipline need to be carried out holistically and continuously, both in the school and family environment, to prepare students to succeed.